Para além do dossel: restauração florestal baseada em processos ecológicos - Hummel, Rafaela Badinelli (2019)
To evaluate if the ecological succession of a given location is directed towards self- sustainability, is necessary to look beyond the trees present in the canopy, where individuals are already established and there is little successional dynamics. Forest structure monitoring is necessary, but it is not enough to detect how ecological processes are working and contribute to the success of restoration projects. This paper aims to analyze the functions that natural regeneration and spontaneous species play in the maintenance of ecological processes in restoration areas. The study was conducted in the city of Itaara, Rio Grande do Sul, covering three areas of sources isolated from degradation factors since 2014. The area belongs to Atlantic Forest Biome, Mixed Ombrophilous Forest. In the first paper we evaluate the interaction between plants and floral visitors in an ecological restoration project. The analysis considered the frequency of interactions between plants and floral visitors in a year of monitoring, analyzed through mutual networks and calculations referring to the structure of networks. Senecio brasiliensis, Miconia hiemalis, Eryngium horridum and Baccharis trimera were the species that presented the greatest number of interactions with flower-visitors. Apis mellifera, Vespidae, Palpada sp., Augloshora sp. were the main flower-visitors observed. The area with open vegetation and predominance of herbaceous and shrub species presented the greatest number of ecological interactions, which demonstrates the determinant role of spontaneous species in the maintenance of flower-visitors in early stages of ecological restoration. In the second paper evaluate the changes in functional diversity in areas of passive restoration. The analysis considered regenerating individuals in two areas with different degradation contexts. We calculate the functional and taxonomic diversity in two moments: 2016 and 2018. The area with the highest degradation level showed an increase in functional diversity over the monitored period, which indicates that, after four years of isolation, the effects of degradation that were more active became less restrictive. The results for Shannon index and functional diversity did not converge in determining diversity for areas, indicating that the exclusive use of taxonomic diversity may provide poor predictive results about the actual functioning of ecosystems. The exclusive use of taxonomic diversity can provide little predictive results on the actual functioning of ecosystems. Functional diversity was efficient to indicate modifications due to the isolation between the periods and areas, improving the effectiveness in the monitoring of ecological restoration strategies. In both articles we show how natural regeneration and spontaneous species can favor ecological succession and the functioning of ecosystems in restoration. Studies approaching not only plant species, but the ecological processes involved are of fundamental importance in forest restoration research.